Aplikasi Maslahah Mursalah dalam Perekonomian Islam serta Relevansinya dalam Penetapan Hukum Islam - R, Ratna; Hardiati, Neni (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The problem of murrasa in the field of Islamic sharia economics still requires a strong legal basis to remain in accordance with sharia principles. Therefore, understanding the methods of legal determination of various financial transactions and innovations is a necessity. Maslahah murlah is one of the many methods that can be used to determine this law. This research intends to examine the application of maslahah murlah in Islamic economic activities and as a method of determining law in Islamic economics. The method used is qualitative with a study of literature related to the issue of Muralah. The results of this research are that maslahah murrasa is widely used in muamalah activities or Islamic economics as an innovation in muamalah activities in which there is benefit for humanity. Such as financial transaction activities in financing agreements, profit sharing, and other contract activities that are often used in Islamic economic activities.